Teori Keperawatan Hildegard E Peplau dan Aplikasinya pada Kasus Gangguan Jiwa - Sunardi, Sunardi; Nursanti, Irna (Jurnal Sains, Teknologi dan Kesehatan, 2024)
This literature review explores Hildegard Peplau's Interpersonal Relations Theory in the context of psychodynamic nursing. It outlines the theory's fundamental concepts, emphasizing human, environmental, and health aspects. The case analysis demonstrates the theory's application in managing patient anxiety. Its strengths include enhancing mental well-being, reducing anxiety, and providing better care. However, the theory has limitations, particularly its emphasis on psychological aspects and neglect of the physical environment. The conclusion highlights the importance of integrating a holistic approach to enhance nursing care effectiveness.